Uwagi o Dyslokacjach w Niejednorodnych i Izotropowych Pierścieniach Kołowych o Zmiennej Grubości - G. Das (Engineering Transactions, 1965)
Through dislocations of various types in isotropic hollow cylinders and circular rings have received much attention (cf. Love, p. 221), it is believed that no problem of dislocation concerned with non-homogeneous material or that concerning isotropic circular ring of varying thickness has yet been solved. In this note a dislocation problem of a circular ring possessing a simple type of non-homogeneity and a dislocation problem of a circular ring of isotropic material with thickness varying inversely as the square of the distance from the centre of the ring have been considered.